Duloxetine and cardiovascular adverse events: A systematic review and meta-analysis. (May 2020) - Park, Kyounghoon; Kim, Seonji; Ko, Young-Jin; Park, Byung-Joo
Abstract: Duloxetine has been increasingly administered, but the associated cardiovascular adverse event risk is not clearly understood. Therefore, we identified the association between duloxetine and cardiovascular adverse events through an analysis of heart rate and blood pressure change. We searched PubMed, EMBASE, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, and psycINFO in June 2019. The title, abstract, and full text were checked in order to obtain articles. A meta-analysis was conducted with random effect model and quality of articles was evaluated using Cochrane Risk of Bias 2.0. The manuscript has been written according to the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) harm checklist. A total of 4009 studies were screened by the title and abstract. After reviewing 186 full texts, 17 studies were finally selected for the meta-analysis. Nine of the 17 studied duloxetine given for mood disorders and 8 for pain control. The duration of 14 studies was under 13 weeks. Cardiovascular adverse events (hypertension, myocardial infarction, transient ischemic attack, tachycardia atrial fibrillation, and cerebrovascular accident) were reported. The meta-analysis demonstrated that duloxetine increased heart rate by 2.22 beats/min (95% confidence intervals [CIs]: 1.53, 2.91) and diastolic blood pressure by 0.82 mmHg (95% CI: 0.17, 1.47). Our findings may be the signal for the safety of cardiovascular disease for short-term use of duloxetine. Well-designed pharmaco-epidemiological studies evaluating the causal relationship between long-term use of duloxetine and cardiovascular disease is still necessary.